USAGE OF ICT IN DEVELOPING ADULT'S COMMUNICATIVE COMPETENCE IN A FOREIGN LANGUAGE - Angela SÎRGHI (Moldova State University, 2020)
In the modern age of science and technology, there is a rapid development and transformation in all the sectors that imply the progress and welfare of people, because everything is modernized and digitized. Last but not least, inventions and new technologies could strengthen and influence not only the economy but also the educational system because they have become part of the educational institutions not only for training students but also for training employable people. In this case, information and communication technologies play a vital role in improving students' knowledge by exposing them to recent materials and events. We must note that regardless of the profession a person can exercise or the titles he holds, it is extremely important to be able to express his opinions, ideas and knowledge. Therefore, for success, communicative competence plays a very important role, which is in fact a complex skill, which requires the simultaneous use of a number of different abilities. The use of ICT can contribute to the development of communication skills by improving speech skills, which not only include the accuracy of pronunciation, but also an adequate fluency and effective communication.   VALORIFICAREA UTILIZĂRII TIC ÎN FORMAREA COMPETENȚEI DE COMUNICARE ÎN LIMBA STRĂINĂ LA ADULȚI În epoca modernă a științei și tehnologiei se atestă o dezvoltare și o transformare rapidă în toate sectoarele ce implică progresul și bunăstarea oamenilor, datorită faptului că totul este modernizat și digitalizat. În cele din urmă, invențiile și noile tehnologii  ar putea să consolideze și să influențeze nu doar economia, dar și sistemul educațional, deoarece au devenit parte a instituțiilor de învățământ nu doar pentru instruirea studenților, ci și pentru a pregăti persoane angajabile. În acest caz, tehnologiile informaționale și de comunicare joacă un rol vital în ce privește îmbunătățirea cunoștințelor studenților prin expunerea lor la materiale și evenimente recente. Trebuie remarcat faptul că, indiferent de profesia pe care o persoană o poate exercita sau de titlurile pe care le deține, devine extrem de important să poată să-și exprime opiniile, ideile și cunoștințele sale. Prin urmare, pentru a avea succes, competența de comunicare atât în limba maternă, cât și în limba străină, joacă un rol foarte important, fiind, de fapt, o abilitate complexă ce necesită utilizarea simultană a unui număr de diferite abilități. Utilizarea  TIC poate contribui la dezvoltarea competenței de comunicare în limba străină prin îmbunătățirea abilităților de vorbire, care includ nu doar acuratețea pronunțării, ci și o fluență adecvată și o comunicare eficientă.